Sjunkande pH i Västerbottens humuslager - Herbertsson, Sofia (2005)
Acidification is a central concept in the environmental debate. The effect of acidification of the soil is a matter of a decreasing amount of cations and thereby a decreasing ability to resist a supply of hydrogen ions to the soil. Acidification has gradually increased in the O horizon in Västerbotten over a 30-year period from the 1970th to the 1990th. The aim of this study was from inventories of The Swedish National Forest Soil Survey and The Swedish National Forest Inventory explain and quantify the acidification that has occurred in the O horizon of two regions in the north of Sweden. Data from SMHI, The Swedish Meteorological and Hydrological Institute, has also been used. The northern region showed a more distinct decrease of pH(H2O) in the O horizon then in the southern region. However, both of the region had significantly pH(H2O) decreases. Acidification processes like biological uptake of ions, biomass distribution and deposition was investigated, but these didn't explain the changes between the regions. A possible process that was investigated and might be explaining the changes of soil chemistry in O horizon is the amount of humus. The southern region had a tendency of decrease and the northern region a tendency of increase of the humus amount.